Analysis of prenatal care that is provided to pregnant women in the province of Heredia who give birth in the San Vicente de Paul Hospital - Alfaro Vargas, Nathalie (2014)
This article presents the main results of a quantitative research design with a non- experimental descriptive cross, which aimed to analyze prenatal care that is provided to pregnant women in the province of Heredia who gave birth at St. Vincent Hospital de Paul in 2012. The population consisted of pregnant women who delivered at the hospital between the months of December 2011 to November 2012 and by medical professionals and nurses whowork for the health areas of Heredia and San Vicente de Paul Hospital, which provide prenatal control. To collect information three instruments considered infrastructure, equipment and procedures to carry out prenatal care, in addition, the level of satisfaction of pregnant women and the professionals were used. The investigation determined that the infrastructure to provide the prenatal control of health areas in the province of Heredia is in good condition, however, requires maintenance and suitability to be accessible to the entire population. Furthermore, the Costa Rican Social Security has a low coverage of antenatal care with compliance with quality criteria and otherwise report the information obtained during the prenatal control in the Perinatal Carnet is incomplete and incorrect. Finally there is little or almost no participation of professionals and Gynecological Nursing, Obstetric and Perinatal, in the process of prenatal care , although national legislation and recognize that these studies and these professionals have the necessary skills to provide adequate control